The sociotechnical walkthrough – a methodological approach for platform studies - Jasmin Troeger; Annekatrin Bock (Studies in Communication Sciences, 2022)
The increasing use of platforms and the availability of data are driving the media and communication transformation in society. Platformization, namely “the penetration of infrastructures, economic processes, and governmental frameworks of platforms in different economic sectors and spheres of life” (Poell, Nieborg, & van Dijck, 2019, p. 5), poses enormous challenges for communication research which deals with data flows, data usage, and the media practices intertwined with platform use. Against the background of the change in digital communication brought about by datafication and platformization, we turn to previous research on platforms and studies applying walkthroughs. We discuss the application of the walkthrough approach at the intersection of science and technology studies (STS) and social semiotic technology research (SST), raising methodological questions for the future study of adaptive learning platforms for illustration. We illustrate the sociotechnical walkthrough as a methodological approach, using our analysis of an adaptive learning platform (Area9) and the associated usage practices. Our analysis features the application of different research personae in order to grasp algorithmic personalization. We conclude with a critical reflection on how the sociotechnical walkthrough approach could fit into a toolkit of traditional and digital methods for future interdisciplinary communications research.